Social entrepreneurial orientation and social value of nonprofit organisation during crises - Samad, Nur Hayati Ab; Ahmad, Noor Hazlina; Ismail, Rina Fadhilah (Edelweiss Applied Science and Technology, 2024)
This study investigates the effect of social entrepreneurial orientation (SEO) on social value for nonprofit organisations (NPOs). SEO denotes a behavioural orientation and embodies a strategic entrepreneurial stance at the organisational level. NPOs practice SEO to ensure organisational sustainability due to resource constraints, especially during crises. The researchers gathered data from 159 NPOs registered under the Registrar of Society (ROS) in Malaysia through a survey questionnaire amid the global COVID-19 pandemic. For data analysis, we employed IBM SPSS 27 to gather organisational profiles. This study used the variance-based structural equation modelling approach via SMART PLS for hypothesis testing. This study treats SEO as a higher-order construct comprising five first-order dimensions of innovativeness, proactiveness, risk management, effectual orientation, and social mission orientation. The study’s findings reveal that SEO significantly and positively influences social value, indicating that SEO improves the social service delivery of NPOs. This study contributes to the nonprofit literature by providing empirical evidence from the social resource-based view (SRBV) theory of the role of SEO on social value, specifically during the crisis. By understanding the role of SEO in value creation, NPOs and regulatory authorities can formulate more precise and impactful strategies to augment the social value of NPOs. Consequently, when NPOs remain sustained, they can continuously provide services to the affected and vulnerable community.